Ekonomi Digital Global dan Pergeseran Pusat Bisnis Dunia Terhadap Pertumbuhan Ekonomi - Sitorus, Alfonso P; Remus Silalahi (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
The development of the global digital economy has become a major driver of the transformation of the world's economic structure and has accelerated the shift of global business centers from developed countries towards the Asian region. Indonesia, as a developing country with a continuously increasing rate of digital technology adoption, has a strategic opportunity to leverage this phenomenon to boost national economic growth. This study aims to analyze the role of the global digital economy and the shift in global business centers on Indonesia's economic growth from the perspective of management science. The research method employed is a qualitative approach with a systematic literature review of nationally accredited SINTA journals, official reports from government agencies, and relevant publications from the 2020–2025 period. The results of the study indicate that the digital economy significantly contributes to economic growth through increased productivity, operational efficiency, expanded market access, and enhanced competitiveness. The shift in global business centers also opens up opportunities for increased investment and Indonesia's integration into global value chains. However, the digital infrastructure gap and limited human resource competency remain major challenges. This research is expected to serve as a reference for policymakers and management practitioners in formulating strategies for sustainable digital economy development.